2010
DOI: 10.1002/acr.20283
|View full text |Cite
|
Sign up to set email alerts
|

Abatacept improves health‐related quality of life, pain, sleep quality, and daily participation in subjects with juvenile idiopathic arthritis

Abstract: Objective. To assess health-related quality of life (HRQOL) in abatacept-treated children/adolescents with juvenile idiopathic arthritis (JIA).Methods. In this phase III, double-blind, placebo-controlled trial, subjects with active polyarticular course JIA and an inadequate response/intolerance to >1 disease-modifying antirheumatic drug (including biologics) received abatacept 10 mg/kg plus methotrexate (MTX) during the 4-month open-label period (period A). Subjects achieving the American College of Rheumatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 34 publications
6
53
0
7
Order By: Relevance
“…An evaluation of 521 children treated with methotrexate for six months reported dramatic improvements in pain, physical function and ability to participate in activities (57). Similar improvements have been demonstrated after treatment with etanercept (58) and abatacept (59).…”
Section: Pharmacological Managementmentioning
confidence: 66%
“…An evaluation of 521 children treated with methotrexate for six months reported dramatic improvements in pain, physical function and ability to participate in activities (57). Similar improvements have been demonstrated after treatment with etanercept (58) and abatacept (59).…”
Section: Pharmacological Managementmentioning
confidence: 66%
“…Традиционные иммунодепрессанты и инги-биторы ФНО ␣ при этом варианте заболевания не всегда эффективны [2][3][4][5][6][7][8]. Длительное применение глюкокор-тикоидов приводит к развитию тяжелых нежелательных явлений и не предотвращает развития деструктивных изменений в суставах [37].…”
Section: Discussionunclassified
“…На фоне лечения отмечено статистически значимое снижение СОЭ, сыво-роточной концентрации СРБ (рис. 4,5).…”
Section: оригинальная статьяunclassified
See 1 more Smart Citation
“…However, multiple sclerosis was found in one patient (39). In another study, improvement was shown in the measurements of quality of life (40). It has been recommended by ARC in cases of unresponsiveness to tumor necrosis factor-alpha inhibitors (41).…”
Section: Treatments Targeting T Cells and B Cells T Abataceptmentioning
confidence: 99%